Association of Body Mass Index on Surgical Outcomes and Cervical Alignment Following Posterior Fusion Surgery for Multilevel Cervical Spondylotic Myelopathy. (16th November 2020) - Fatima, Nida; Shin, John H
Abstract: INTRODUCTION: With the increasing prevalence of obesity, there is a need to understand the impact of body mass index (BMI) on spine surgery outcomes. METHODS: A retrospective chart review of 275 patients who underwent decompressive cervical laminectomy and bicortical lateral mass screw-rod arthrodesis for degeneration at an academic tertiary care hospital between 2012–2019 was performed. Patients were categorized into 3 groups based upon the BMI as (i) normal weight (<25.0kg/m 2, 28.4%), (ii) overweight (25.0-29.9kg/m 2, 42.5%), and (iii) obese (≥30.0kg/m 2, 29.1%). For each BMI cohort, univariable association with postoperative outcomes were first determined using logistic regression, and a predictive model was then constructed using all characteristics significant at the 0.10 alpha level. All associations were reported as odds ratio (OR) with 95% confidence interval (CI). RESULTS: Patients with higher BMI were associated with an increased risk of postoperative distal junctional kyphosis (OR:2.12, 95%CI:1.07-4.19; P = .03) and Nurick grade (>1) (OR:1.61, 95%CI:1.01-8.21; P = .05). Furthermore, adjusted multivariable regression analysis revealed that obese patients had a 2.32-folds higher likelihood of postoperative C2-C7 sagittal vertical Axis>40mm (OR:2.32, 95%CI:1.01-5.44; P = .04) and 1.31-folds higher risk of T1 slope minus C2-C7 lordosis (T1S-CL) ≥25 (OR:1.31, 95%CI:1.12-5.69; P = .05). However, patients under BMI<25.0 kg/m 2 had 63% less likelihood of postoperative T1S-CL≥25 (OR:0.37, 95%CI:0.13-1.02; P = .05). CONCLUSION: Our results corroborated that the patients with higher BMI are at an increased risk of neurological dysfunction, complications and cervical misalignment following posterior fusion surgery for DCSD.